Determinant Analysis of Decrease In Manufacturing Export Value Amid Depreciation of Rupiah Exchange Rate - Nanik Ika Nurhayati (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2017)
Indonesia uses a system of floating exchange rate. The depreciation of the exchange rate, in which the value of domestic currency decreases and the value of foreign currency increases, will increase the export. The high depreciation of Rupiah should be able to increase the competitiveness of Indonesia’s export products, especially the manufacturing exports that have the greatest contribution to the total exports. However, what has happened in recent years is very different. The depreciation of Rupiah value cannot spur the value of Indonesia’s manufacturing exports. Based on the fact above, the research is entitled